Evaluation of vertical jumping performance under the perspective of principal component analysis - Kollias, I.; Panoutsakopoulos, V.; Papaiakovou, G.; Giatsis, G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Multiple regression analysis techniques have been used in the past [1] in an attempt to identify the most critical parameters determining vertical jumping (VJ) performance. The use of Principal Components Analysis (PCA), however, incorporates a large number of variables, highly correlated to each other, by a smaller number of computed factors [2]; thus, it has been shown that it could be a useful tool to evaluate vertical squat jumping [3]. The purpose of the present study was to explore whether PCA could be applied to examine a possible tendency of temporal or peak force dependency among groups of athletes executing different types of VJ. Methods 11 male international-level jumpers (TF; 22.9±4.5yrs; 1.87±0.05m; 76.6±6.7kg), 10 male professional volleyball players (VB; 23.9±4.4yrs; 1.94±0.03m; 85.7±7.0kg) and 14 male professional soccer players (SO; 25.3±4.2yrs; 1.82±0.06m; 78.7±7.4kg) executed a) squat jumps with the use of arms (SQJA), b) countermovement jumps with (CMJF) and without the use of arms (CMJA) and c) drop jumps from 60cm without the use of arms (DJ60A) on an AMTI OR6-5-1 force plate (AMTI, Newton, MA). Data (sampling frequency: 500Hz) were stored in a 486 DX personal computer. A PCA with Varimax Rotation on the exerted dynamic parameters was conducted using the SPSS 10.0.1 software (SPSS Inc., Chicago, Il.). PCA scores were statistically analysed using one-way ANOVA with a Scheffe Post-Hoc test (p<.05) in order to reveal differences among groups. Results PCA results suggested the existence of two factors of principal components. The first rotated principal component was associated with the temporal characteristics of the VJ, which accounted for 56.0%, 60.3%, 57.2% and 55.3% of the variance of the SQJF, CMJA, CMJF and DJ60A force data, respectively. The second was associated with the peak force characteristics of the VJ, which accounted for 22.3%, 17.5%, 21.6% and 19.9% of the variance of the SQJF, CMJA, CMJF and DJ60A force data, respectively. Comparison of TF, VB and SO are presented in a Table.